Remarks on quantum mechanics and non-reflexive logic - da Costa, Newton (THEORIA. An International Journal for Theory, History and Foundations of Science, 2024)
In this paper we discuss and outline a version of non-relativistic quantum mechanics based on a new non-reflexive logic, where the basic entities (elementary particles) lack identity conditions. Some relationships with quantum field theories are also sketched.